Protective effects of crude chalaza hydrolysates against liver fibrogenesis via antioxidation, anti-inflammation/anti-fibrogenesis, and apoptosis promotion of damaged hepatocytes - Yi-Ling Lin; Ching-Fu Lu; Yi-Hsieng Samuel Wu; Kuo-Tai Yang; Wen-Yuan Yang; Jr-Wei Chen; Jung-Kai Tseng; Yi-Chen Chen (Poultry Science, 2021)
ABSTRACT: Four-hundred metric-ton chalazae are produced annually from the liquid-egg processing and always cause a heavy burden due to handling cost in Taiwan. After chalazae were hydrolyzed by protease A, the amounts of hydrophobic, aromatic, and branched-chain amino acids, as well as anserine were dramatically increased. This study was to understand the antifibrogenic effects of protease A-digested crude chalaza hydrolysates (CCH-As) on livers of thioacetamide (TAA) treated rats. CCH-As improved (P< 0.05) growth performance, serum liver damage indices, histopathological liver inflammation, and liver collagen deposition in TAA-treated rats. The antifibrogenic effects of CCH-As were due to decreased (P < 0.05) inflammatory/fibrogenic cytokine contents, α-smooth-muscle-actin (α-SMA) protein expression, and matrix metallopeptidase (MMP)-2 and -9 activities, as well as increased (P < 0.05) the antioxidant capacity in livers. CCH-As also increased (P < 0.05) cleaved caspase-3 and cleaved poly ADP-ribose polymerase protein levels in livers of TAA-treated rats which accelerating cell renewal. Thus, this study does not only reveal a novel nutraceutical ingredient, CCH-As, against liver fibrogenesis, but also offer an alternative way to expand the utilization of poultry byproducts.